(untitled) (Journal of the Sociology and Theory of Religion, 2021)
In our contemporary society the understanding and communication of faith faces diverse challenges. One of these challenges is posed by scientific reductionism, which is widespread worldwide, and questions the rationality of all religious instruction. One of the objectives of religious teaching in schools is not only the passing on of the Christian message but also to place it in dialogue with other aspects of contemporary education. The bare exchange that occurs in the conversation between religion and science is surprising, as well as the one-way approach from religion to science, when the need for such a dialogue is a subject that has been addressed by a diverse range of Christian churches in recent decades. We also witness very valuable contributions to Christian theology by scientists of international stature (J. Polkinghorne, G. Ellis, A. Peackocke, S. Harding, etc.).